Advanced Human Immunodeficiency Virus Disease at Diagnosis in Mozambique and Swaziland. (23rd July 2017) - Kujawski, Stephanie A; Lamb, Matthew R; Lahuerta, Maria; McNairy, Margaret L; Ahoua, Laurence; Abacassamo, Fatima; Nuwagaba-Biribonwoha, Harriet; Gachuhi, Averie; El-Sadr, Wafaa M; Elul, Batya
Abstract: Background: Early diagnosis of human immunodeficiency virus (HIV) is a prerequisite to maximizing individual and societal benefits of antiretroviral therapy. Methods: Adults ≥18 years of age testing HIV positive at 10 health facilities in Mozambique and Swaziland received point-of-care CD4 + cell count testing immediately after diagnosis. We examined median CD4 + cell count at diagnosis, the proportion diagnosed with advanced HIV disease (CD4 + cell count ≤350 cells/μL) and severe immunosuppression (CD4 + cell count ≤100 cells/μL), and determinants of the latter 2 measures. Results: Among 2333 participants, the median CD4 + cell count at diagnosis was 313 cells/μL (interquartile range, 164–484), more than half (56.5%) had CD4 + ≤350 cells/μL, and 13.9% had CD4 + ≤100 cells/μL. The adjusted relative risk (aRR) of both advanced HIV disease and severe immunosuppression at diagnosis was higher in men versus women (advanced disease aRR = 1.31; 95% confidence interval [CI] = 1.16–1.48; severe immunosuppression aRR = 1.54, 95% CI = 1.17–2.02) and among those who sought HIV testing because they felt ill (advanced disease aRR = 1.30, 95% CI = 1.08–1.55; severe immunosuppression aRR = 2.10, 95% CI = 1.35–2.26). Age 18–24 versus 25–39 was associated with a lower risk of both outcomes (advanced disease aRR = 0.70, 95% CI = 0.59–0.84; severe immunosuppression aRR = 0.62, 95% CI = 0.41–0.95). Conclusions: More than 10 years into the global scale up of comprehensive HIV services, the majority of adults diagnosed with HIV at health facilities in 2 high-prevalence countries presented with advanced disease and 1 in 7 had severe immunosuppression. Innovative strategies for early identification of HIV-positive individuals are urgently needed.